Application hybrid GSAPSO Technique for AGC in Inter Connected Power System with Generation Rate Constant (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An attempt has been taken in this work to effectively implement the combination ofGSA and PSO (hGSA-PSO) technique towards AGC in two-area inter-connected power systemswith generation rate constraint (GRC) is considered. For the design and analysis, a initialattempt has been taken to optimize parameters of proportional-integral-derivative (PID)controller in two area non-reheat thermal power system employing GSA and hGSA-PSOalgorithm with ITAE objective function. A sensitivity studies carried out for the robustness ofthe system by changing the operating condition and variation of the parameter and generationrate constant (GRC= ±0.05 and ±0.025) is considered. The performances of the proposedcontroller has been evaluated with those of some previously published optimization techniquessuch as GA and BOFA based optimized controller parameters for the same power system. Thisstudy of the present work is extended to two area multi sources power system to test therobustness analysis of the system by comparing the hGSA-PSO optimized to PI controller withsame structure of system by selecting with and without GRC for showing the dynamicperformance analysis of the system in term of settling time and overshoot.